Analysing Factors that Influence Economic Growth in South Africa. Factors Influencing Economic Growth - Hlapi, Amanda; Stiglingh-Van Wyk, Abigail; David, Oladipo Olalekan (Acta Universitatis Danubius. Œconomica, 2023)
Since achieving high economic growth in South Africa persists as one of the ultimate serious development issues, it is critical to examine factors that influence South African economic growth. Using Autoregressive Distributed Lag (ARDL), the study was conducted to analyse the variables influencing South African economic growth from 1990 to 2021. The study discovers that technological progress, labour, power supply, and capital formation are all associated significantly with South African economic growth. According to the research, in the long run, labour and technological progress coefficients are positively correlated with economic growth, whereas power supply and human capital are negatively correlated. These findings have significant policy implications. According to the study's findings, it is advised that appropriate policies be created to support the industries that help South Africa's economy flourish. Strategies to be endorsed should include those that captivate such as improving the quality of education to increase human capital and greater investment mostly in the infrastructure of the electricity supply industry are crucial for resolving the issue of electricity supply since doing so would force South Africa to experience long-term economic growth.